JWST Discovery of a Very Fast Biconical Outflow of Warm Molecular Gas in the Nearby Ultraluminous Infrared Galaxy F08572+3915 NW - Kylie Yui Dan; Jerome Seebeck; Sylvain Veilleux; David Rupke; Eduardo Gonzalez-Alfonso; Ismael Garcia-Bernete; Weizhe Liu; Dieter Lutz; Marcio Melendez; Miguel Pereira Santaella; Eckhard Sturm; Francesco Tombesi (The Astrophysical Journal)
We present new James Webb Space Telescope (JWST) Mid-Infrared Instrument Medium-Resolution Spectrometer observations of the nearby ultraluminous infrared galaxy (ULIRG) F08572+3915 NW. These integral field spectroscopic (IFS) data reveal a kpc-scale warm-molecular rotating disk and biconical outflow traced by the H _2 ν = 0–0 S(1), S(2), S(3), and S(5) rotational transitions. The outflow maintains a relatively constant median (maximum) projected velocity of 1100 km s ^−1 (3000 km s ^−1 ) out to ∼1.4 kpc from the nucleus. The outflowing H _2 material is slightly warmer (640–700 K) than the rotating disk material (460–520 K), perhaps due to shock heating in the highly turbulent outflowing material. This outflow shares the same kinematics and orientation as the sub-kiloparsec scale warm H _2 outflow traced by the rovibrational H _2 lines in Keck AO near-infrared IFS data. However, this warm H _2 outflow is significantly faster than the sub-kiloparsec-scale cold molecular outflow derived from multi-transition far-infrared OH observations with Herschel and the greater than or equivalent to kiloparsec-scale cold molecular outflow mapped by millimeter-wave interferometric CO 1–0 observations with IRAM-PdBI and NOEMA. The new JWST data bolster the scenario where the buried quasar in this ULIRG is excavating the dust screen, accelerating perhaps as much as 60% of the dusty warm molecular material to velocities beyond the escape velocity, and thus influencing the evolution of the host galaxy.